2020
DOI: 10.1128/msphere.00534-20
|View full text |Cite
|
Sign up to set email alerts
|

The Fungal Microbiome Is an Important Component of Vineyard Ecosystems and Correlates with Regional Distinctiveness of Wine

Abstract: The flavors of fermented plant foods and beverages are formed by microorganisms, and in the case of wine, the location and environmental features of the vineyard site also imprint the wine with distinctive aromas and flavors. Microbial growth and metabolism play an integral role in wine production, by influencing grapevine health, wine fermentation, and the flavor, aroma, and quality of finished wines. The contributions by which microbial distribution patterns drive wine metabolites are unclear, and while flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
86
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 75 publications
(137 reference statements)
13
86
1
1
Order By: Relevance
“…Although dominant phyla were consistently found in the six regions tested, they were present in different ratios. This finding is similar to earlier work; for example, investigating Pinot Noir vineyards in regions of Victoria and South Australia, Australia, Liu et al (2020) found the same nine top dominant bacteria groups. However, in Australian agricultural soils, Bissett et al (2010) found top six dominant soil bacteria groups (>3% occurrence) are slightly different and Cyanobacteria replacing Planctomycetes, Chloroflexi, Gemmatimonadetes, and Verrucomicrobia ( Bissett et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Although dominant phyla were consistently found in the six regions tested, they were present in different ratios. This finding is similar to earlier work; for example, investigating Pinot Noir vineyards in regions of Victoria and South Australia, Australia, Liu et al (2020) found the same nine top dominant bacteria groups. However, in Australian agricultural soils, Bissett et al (2010) found top six dominant soil bacteria groups (>3% occurrence) are slightly different and Cyanobacteria replacing Planctomycetes, Chloroflexi, Gemmatimonadetes, and Verrucomicrobia ( Bissett et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that environmental factors (e.g., climate and soil properties) and crop management may affect microbial populations in vineyards ( Burns et al, 2015 ; Gupta et al, 2019 ; Liu et al, 2020 ). To date, the largest number of vineyards included in a single vineyard microbiome study is 15 ( Liu et al, 2020 ). Here the authors made a thorough examination of the contribution of microbial communities to wine regionality at a supra-regional level (up to 400 km) and identified the fungal microbiome as a potential driver of terroir.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations